Charge-symmetric description of electrons and positrons in the Dirac theory without negative energies - Poluektov, Yu.M. (Вопросы атомной науки и техники, 2020)
A formulation of the Dirac theory, symmetric with respect to particles and antiparticles, in which negative energy states are excluded, is proposed. Fields of particles and antiparticles are associated with wave functions for which the Born interpretation as probability amplitudes is valid. Thus, in theory, various “paradoxes” are eliminated, the existence of which is due to incorrect accounting of states with negative energy. Запропоновано симетричне щодо частинок і античастинок формулювання теорії Дірака, в якій відсутні стани з від’ємною енергією. Полям частинок і античастинок зіставлені хвильові функції, для яких справедлива борнівська інтерпретація як амплітуд імовірності. Тим самим у теорії усуваються різноманітні «парадокси», існування яких обумовлено некоректним урахуванням станів з від’ємною енергією. Предложена симметричная относительно частиц и античастиц формулировка теории Дирака, в которой отсутствуют состояния с отрицательной энергией. Полям частиц и античастиц сопоставлены волновые функции, для которых справедлива борновская интерпретация как амплитуд вероятности. Тем самым в теории устраняются различные «парадоксы», существование которых обусловлено некорректным учётом состояний с отрицательной энергией.